Micromagnetic Simulation of Round Ferromagnetic Nanodots with Varying Roughness and Symmetry - Steinmetz, Pia; Ehrmann, Andrea (Condensed Matter)
Magnetic nanodots are of high interest for basic research due to their broad spectrum of possible magnetic states and magnetization reversal processes. Besides, they are of technological interest since they can be applied in magnetic data storage, especially if vortex states occur in closed dots or open rings. While producing such nanorings and nanodots from diverse magnetic materials by lithographic techniques is quite common nowadays, these production technologies are naturally prone to small deviations of the borders of these nanoparticles. Here we investigate the influence of well-defined angular-dependent roughness of the edges, created by building the nanoparticles from small cubes, on the resulting hysteresis loops and magnetization reversal processes in five different round nanodots with varying open areas, from a thin ring to a closed nanodot. By varying the orientation of the external magnetic field, the impact of the angle-dependent roughness can be estimated. Especially for the thinnest ring, significant dependence of the transverse magnetization component on the field orientation can be found.
Keywords: OOMMF (Object Orientated MicroMagnetic Framework); nanostructure; iron; vortex state; domain wall; rough borders